Dinamika Urbanisasi dan Sanitasi dalam Menurunkan Stunting dan Meningkatkan Produktivitas - Sulaeman, Maman (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to analyze the relationship between urbanization, sanitation, stunting, and labour productivity in Indonesia. Using panel data from 34 provinces during the 2018-2022 period with a total of 170 observations, this study applies a panel data regression model with a fixed effects approach to identify factors affecting the stunting prevalence and labour productivity in Indonesia. The estimation results show that urbanization levels and access to proper sanitation have a negative and significant effect on stunting prevalence with coefficients of -0.158 and -0.187, respectively. Each 1% increase in urbanization level correlates with a 0.312% increase in access to proper sanitation, while each 1% increase in stunting prevalence correlates with a 0.256% decrease in sanitation access. In the labour productivity determinant model, urbanization and sanitation have positive effects with coefficients of 0.587 and 0.215, while stunting has an adverse impact with a coefficient of -0.342. The research conclusion indicates that well-planned urbanization can improve sanitation access and reduce stunting prevalence, which ultimately contributes to increased labour productivity. The policy implication of this research is the importance of integrating stunting reduction programs with urbanization planning and improved sanitation access as a comprehensive strategy to promote productivity and economic growth.